Effect of zinc on phytoremediation potential and carbonic anhydrase and polyphenol oxidase activities of Lythrum salicaria L. - Bingol, Niiket Akaml; Akin, Betul; Kocacaliskan, Ismail; Nalbantoglu, Barbaros; Meseli, Onur (Tubitak Scientific & Technological Research Council Turkey, 2021)
In this study, Lythrum salicaria plant was tested in hydroponic culture to demonstrate its zinc accumulating capacity and tolerance to different zinc levels. Lythrum salicaria seedlings were grown in 10% Hoagland solution containing 0, 5, 10, 20, 30, 40, 50, 75, and 100 mg/L zinc, and 30 mg/L zinc with different pH levels (5, 6, and 7). Following this, the seedlings were harvested after 1st, 2nd, 4th and 7th days. Zinc caused significant decreases in the relative values of the mean root-shoot length and fresh weight of the plant (92 to 75%; 100 to 92%; 64.2 to 41.2%, respectively), and contents of chlorophyll a, chlorophyll b, total chlorophyll, and carotenoids in the leaf (0.54 to 0.43; 0.16 to 0.11; 0.65 to 0.54; 0.097 to 0.080 mg/g fresh weight, respectively). There were significant increases in zinc accumulation parallel to zinc increase and pH in solution in plant tissues, zinc accumulation in roots (13,659.7 mg/kg dry weight) was higher than in shoots. Leaf protein content (0.31 to 0.49 mg/g fresh weight), and polyphenol oxidase (0.80 to 1.95 mg/g fresh weight), and carbonic anhydrase activities in the roots increased (6.7 to 17.87 mg/g fresh weight).These data indicate that Lythrum salicaria has a high ability to accumulate zinc, so that it may have the potential to be used in zinc remediation projects.
Keywords: Accumulation; chlorophyll; enzyme activity; Lythrum salicaria; protein; zinc; HEAVY-METAL STRESS; LEAD; PLANTS; METABOLISM; TOXICITY; REMOVAL; CADMIUM; NICKEL; GROWTH; Plant Sciences